2014
DOI: 10.1097/sap.0b013e318276d979
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Outcome Analysis of Breast Reconstruction Paradigm Shift

Abstract: Increased bilateral mastectomy for breast cancer treatment has generated an increased demand for bilateral breast reconstruction. This study examines changing patterns of reconstruction over the last decade to accommodate increased case volume and decreased morbidity associated with reconstruction. A single institution series of 3171 consecutive breast reconstruction cases of more than 10 years was divided into 2 periods, that is, 1999 to 2004 and 2005 to 2010. Bilateral breast reconstruction case volume incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…This is consistent with previously reported trends in the United States and Canada . Regression analysis demonstrated that younger patients were significantly more likely to receive immediate breast reconstruction, which is consistent with previous literature . Patients with a cancer diagnosis were also less likely to receive IBR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previously reported trends in the United States and Canada . Regression analysis demonstrated that younger patients were significantly more likely to receive immediate breast reconstruction, which is consistent with previous literature . Patients with a cancer diagnosis were also less likely to receive IBR.…”
Section: Discussionsupporting
confidence: 91%
“…A significant shift in breast reconstruction following mastectomy has occurred in the last decade with an increase in the number of women undergoing mastectomy and immediate implant‐based reconstruction; this is particularly occurring in younger women . One of the challenges with implant‐based reconstruction is the potential need for adjuvant radiation therapy and the subsequent risk of complications, such as reconstruction failure, capsular contracture, infection, implant exposure, and mastectomy flap necrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the United States have shown a dramatic increase in prosthetic breast reconstruction from 40% to 74% 12 , 18 , 19 partly due to the changed mastectomy patterns – a 15% and 12% per year increased application of contralateral and bilateral prophylactic mastectomies. 18 However, this is not the case in China for multiple reasons, such as the lack of public awareness, scientific guidelines, and the feasibility of tests for breast cancer; 1/2 gene mutation, as well as cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of care in Canada show more women are choosing bilateral, single‐stage and prosthesis‐based reconstructions . Though autologous reconstructions have many applications, especially in the delayed or radiated woman, their use in immediate reconstruction has decreased.…”
Section: Discussionmentioning
confidence: 99%